2015
DOI: 10.1007/s10875-015-0164-2
|View full text |Cite
|
Sign up to set email alerts
|

Enteroviral Infection in a Patient with BLNK Adaptor Protein Deficiency

Abstract: B-cell linker (BLNK) protein is a non-redundant adaptor molecule in the signaling pathway activated by (pre) B-cell antigen receptor signals. We present two siblings with a homozygous deleterious frameshift mutation in BLNK, resulting in a block of B cell development in the bone marrow at the preB1 to preB2 stage, absence of circulating B cells and agammaglobulinemia. This is the first description of an enteroviral infection associated arthritis and dermatitis in a patient with BLNK deficiency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 19 publications
1
7
0
Order By: Relevance
“…His symptoms commenced at 8 months of age. Other studies that have found mutant BLNK in association with agammaglobulinemia can be found here [87][88][89]. They confirm recurrent otitis and sinopulmonary infections as the most common initial presentation of BLNK deficiency [88,89].…”
Section: Blnk Deficiencysupporting
confidence: 77%
See 1 more Smart Citation
“…His symptoms commenced at 8 months of age. Other studies that have found mutant BLNK in association with agammaglobulinemia can be found here [87][88][89]. They confirm recurrent otitis and sinopulmonary infections as the most common initial presentation of BLNK deficiency [88,89].…”
Section: Blnk Deficiencysupporting
confidence: 77%
“…They confirm recurrent otitis and sinopulmonary infections as the most common initial presentation of BLNK deficiency [88,89]. However, other clinical manifestations included diarrhea, enteroviral infection, arthritis, dermatitis, and bronchiectasis [89].…”
Section: Blnk Deficiencymentioning
confidence: 64%
“…On the other hand, macrophage migration inhibitory factor (MIF) which is important for the acute immune response [35] was significantly downregulated as well as chemokine C-C motif receptor 1 (CCR1) playing a role in recruitment of leukocytes to the effector site [36] (fold change = 0.45 and 0.36, respectively). Furthermore, sialic acid binding Ig-like lectin 10 (SIGLEC10) which is a negative regulator of immune signaling by functioning as an inhibitory receptor [37] and B cell linker (BLNK) , an adaptor molecule linked to the pathway activated by B-cell antigen receptor signals [38], were significantly downregulated, with fold changes of 0.01 and 0.26, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…To date, 6 patients with mutations in the scaffold protein BLNK have been described (5255). These patients lack expression of BLNK as they harbor either nonsense or frameshift mutations, generally having clinical findings that are comparable to those seen in patients with mutations in BTK.…”
Section: Discussionmentioning
confidence: 99%